Commercially Important Medicinal Plants of Kanatal Forest Tehri-garhwal - Uniyal, M. R.; Issar, R. K. (Indian Forester, 1967)
A systematic survey of 15 commercially important medicinal plants of Kanatal forest in Tehri-garhwal was conducted during the year 1963-64. Data was collected relating to their general description, trade/Indian name, distribution, time and method of collection, availability, part or parts used as crude drugs, local folklore, their exploitation on commercial lines and market studies.